The Effects of Selenium Nanoparticles on the Osseointegration of a Titanium Implant in Rabbits: A Histomorphometric Investigation - Osama A.R. Alheeti; Ghasak H. Jani; Farah Ragheed Qustanteen (University Library System, University of Pittsburgh, 2024)
Objective: One of the unique tooth or tooth replacement prosthesis in the dental implant. To encourage bone formation where it is applied, our approach uses a biomaterial system that is easily obtainable, and able to induce osteoinductive growth factor. Selenium nanoparticles are Methods: Thirty-two implants consisting of commercially pure titanium rod were given to sixteen New Zealand rabbits. One implant was placed in each tibia of each rabbit. After implantation, eight rabbits were sacrificed every one to six weeks. For each animal, the left tibia implant was treated with selenium nanoparticles, whereas the right tibia implant was left uncoated. After staining each section with hematoxylin and eosin, the sections were examined histologically and assessed for histomorphometric analysis, which counted the number of bone particles that were formed. Results: Selenium nanoparticle-coated titanium implants showed earlier bone growth, mineralization, and maturation than control comparisons. After all the bone parameters were examined histomorphometrically for the study, the healing durations of the two types of implants differed significantly. Conclusion: Selenium nanoparticle-coated titanium implants had improved healing and osseointegration.